2019
DOI: 10.1002/uog.20860
|View full text |Cite
|
Sign up to set email alerts
|

First‐trimester intervention in twin reversed arterial perfusion sequence

Abstract: What are the novel findings of this work? Early intrafetal laser therapy in pregnancy with twin reversed arterial perfusion (TRAP) sequence does not increase fetal-loss rate, resulting in 92% live births, and it may be advantageous in comparison to waiting until a more advanced gestational age. Our findings are in partial contrast to those of a previously published study, in which fetal-loss rate was comparatively high at 42%. What are the clinical implications of this work? Our findings support first-trimeste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
49
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 10 publications
2
49
0
4
Order By: Relevance
“…They also identified gestational age at intervention and discordance between crown-rump length (CRL) of the pump twin and upper pole-rump length of the TRAP twin, measured as (CRL-URL)/CRL ratio and URL/CRL ratio, as predictive factors of pregnancy outcome. 22 A very recent work by Tavares de Sousa et al 23 reports a live birth rate of 92% at a median gestational age of 39 +6 (interquartile range 37 +1 to 41 +2 ) weeks in 12 TRAP cases treated before 14 +3 weeks. These differences in outcome may possibly be explained by variation in inclusion criteria, operative technique, as well as gestational age and fetal size even in the narrow interval between 11 and 15 weeks.…”
Section: Timing Of Interventionmentioning
confidence: 98%
“…They also identified gestational age at intervention and discordance between crown-rump length (CRL) of the pump twin and upper pole-rump length of the TRAP twin, measured as (CRL-URL)/CRL ratio and URL/CRL ratio, as predictive factors of pregnancy outcome. 22 A very recent work by Tavares de Sousa et al 23 reports a live birth rate of 92% at a median gestational age of 39 +6 (interquartile range 37 +1 to 41 +2 ) weeks in 12 TRAP cases treated before 14 +3 weeks. These differences in outcome may possibly be explained by variation in inclusion criteria, operative technique, as well as gestational age and fetal size even in the narrow interval between 11 and 15 weeks.…”
Section: Timing Of Interventionmentioning
confidence: 98%
“…These findings prompted some centers to prepone the intervention to the 1 st trimester. So far only two studies have reported on TRAP treated in the 1 st trimester [6,7]. They focused on potential predictors for survival following intervention in the 1 st trimester, such as gestational age at intervention, crown-rump length (CRL) of the pump twin, upper pole-rump length (URL) of the TRAP twin, (CRL-URL)/CRL ratio, and URL/CRL ratio.…”
Section: Introductionmentioning
confidence: 99%
“…Clips metálicos. Se colocan clips en el cordón del feto acardio guiado por ecografía 24,31,32 y se realiza ligadura mediante fetoscopia 14,23,33,34 o tras exteriorizarlo por una pequeña histerotomía 26 .…”
unclassified
“…• Láser. Se realiza coagulación con láser 33,[35][36][37] o con fórceps bipolar 32 del cordón del feto acardio.…”
unclassified
See 1 more Smart Citation